Consumer Decision Making Process In Selecting Tourism Destination - F Al-Otaibi, Eman Awwadh (2011)
In this project, the concentration will be on discussing Consumer Decision Making Process in Selecting Tourist Destination. The project\'s theoretical framework is a descriptive category based on theory of consumer decision process model to expound the respondents\' demographic differences depended on pre-purchase, purchase and post-purchases\' consumption and evaluation of public utilities and tourism industrial services, products and promotions to come up with results and recommendations that may contribute to develop Malaysian tourism industrial services.